2015
DOI: 10.1016/j.jprot.2014.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation of hierarchical phosphorylation by protein kinase CK2

Abstract: Phosphorylation is a crucial regulatory mechanism governing cellular signal transduction pathways, and despite the large number of identified sites to date, most mechanistic studies remain focused on individual phosphorylation sites. This study is the first to systematically determine specific consensus sequences for hierarchical phosphorylation events. The results indicate that individual phosphorylation sites should not be studied in isolation, and that larger, multisite phosphorylation motifs may have profo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 42 publications
(56 reference statements)
5
63
0
Order By: Relevance
“…Furthermore, we observed that the C-tail of FGF14 contains a consensus GSK–3 phosphorylation motif ( S/T )XXX(S/T), the first residue in this sequence corresponding to S226. (The phosphorylation motif for GSK–3 contains two serine/threonines: the first, at the P position, corresponds to the site phosphorylated by GSK–3, and the second, at the P + 4 position, corresponds to a priming phosphorylation site that increases the efficiency of GSK–3-dependent phosphorylation (Casaday et al, 2004; St-Denis et al, 2015; ter Haar et al, 2001)). Based on these observations, we conducted an in vitro phosphorylation assay using recombinant GSK–3β with a FGF14 peptide with the sequence KPGVTP S KSTSASAIMNGGK.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we observed that the C-tail of FGF14 contains a consensus GSK–3 phosphorylation motif ( S/T )XXX(S/T), the first residue in this sequence corresponding to S226. (The phosphorylation motif for GSK–3 contains two serine/threonines: the first, at the P position, corresponds to the site phosphorylated by GSK–3, and the second, at the P + 4 position, corresponds to a priming phosphorylation site that increases the efficiency of GSK–3-dependent phosphorylation (Casaday et al, 2004; St-Denis et al, 2015; ter Haar et al, 2001)). Based on these observations, we conducted an in vitro phosphorylation assay using recombinant GSK–3β with a FGF14 peptide with the sequence KPGVTP S KSTSASAIMNGGK.…”
Section: Resultsmentioning
confidence: 99%
“…CK2 is known to phosphorylate its substrates in clusters, with phosphorylation at one site priming the substrate for phosphorylation at additional sites (27,28). The C-terminal region contains two potential Ser clusters: a proximal cluster of S503, S505, and S518 and a distal cluster of S572, S579, and S584 (Fig.…”
Section: Ecd Levels and Localization Do Not Change During Cell Cycle mentioning
confidence: 99%
“…FMRP S499 could be regulated by dephosphorylation alone; however, it has been shown that S499 phosphorylation levels are not affected by PP2A, the putative FMRP phosphatase (Bartley et al, 2014). A recent exhaustive study has shown that although CK2 is constitutively active, it can promote secondary hierarchical phosphorylation by other kinases, many of which are regulated in a signal-dependent manner (St-Denis et al, 2015). This supported our hypothesis that phosphorylation of FMRP S499 is permissive for secondary phosphorylation of FMRP.…”
Section: Introductionmentioning
confidence: 99%